The Effect of High Intensity Interval Training (HIIT) on Reaction Time Study Among Medical Student in Semarang - Chikita Dian Rahma Saphira; Sumardi Widodo; Arinta Puspita Wati; Tanjung Ayu Sumekar (Jurnal Kedokteran Diponegoro, 2021)
Background: Reaction time is a cognitive-motoric connection that is important in making quick decisions. Due to the lack of time, medical student has low physical activity.  High Intensity Interval Training (HIIT) is a strong and intense exercise interspersed with low intensity exercise that does not require much time. It has been known that can improve cognitive function.